The Effect of STEM Learning Approach on Students' Mathematical Problem-Solving Ability - Rais, Hidayati; Ramadhani, Ramadhani; Yassin, Abdulnassir (Vocational: Journal of Educational Technology, 2025)
This study aims to describe mathematical problem-solving skills before and after being taught using the STEM learning approach better than Conventional learning. Using a quantitative approach, quasi-experimental method with posttest-only control design. The population of this study was class VIII students with 7 classes totalling 151 students, through simple random sampling to provide equal opportunities to be selected as samples, 27 students from class VIII E experimental group and 22 students from class VIII A control group. Data collection techniques using mathematical problem-solving ability essay test. Data analysis was carried out normality test using Kolmogorov-Smirnov formula and homogeneity test using F test. The results of data analysis obtained normal distribution data and homogeneous variants, then the hypothesis test using t-test obtained t-count= 2.3921 greater than t-table= 1.6779 at the significance level ?= 0.05. It is concluded that the ability to solve mathematical problems taught using the STEM learning approach is better than using Conventional learning for class VIII students of SMP Negeri 12 Merangin in the 2024/2025 academic year. This study implies that the STEM approach can be an effective strategy to improve students' mathematical problem-solving skills.